PENGEMBANGAN MEDIA PEMBELAJARAN BAHASA ARAB DI KELAS BILINGUAL SMA TAKHASUS AL-QUR’AN WONOSOBO - Putri Bunga, Ajeng; Alfi Nurjanah, Eka Saputri; Jayanti, Arum Dewi; Maulana, Dimas Putra; Idatunnisa, Isma; Aini, Fina Qurrotul; Nurcholisho, Lilik Rochmad (DAS Institute, 2023)
SMA Takhassus Al-Qur’an is a pesantren-based school that has a language program called the bilingual class to create a language environment (al biiah al lughowiyah). The learning process emphasizes mastering the basic knowledge of Arabic, then applying and developing it. The aim of this research is to describe the implementation of the bilingual class program, and to identify the supporting and inhibiting factors. This research is descriptive qualitative in nature. Observation, interviews, and documentation are the data collection techniques used. The results of this research indicate that the Arabic day program is an additional activity carried out outside the classroom to help students understand and get used to speaking Arabic. The implementation of the bilingual class program begins with three stages: planning the preparation of learning materials based on students' needs in the form of vocabulary books. The implementation of the bilingual class program is carried out with a different learning concept in the classroom, where learning materials are packaged in a simple manner, and the teaching methods and models are innovative, creative, and enjoyable. Then, evaluations are conducted before (Pretest) and after activities (Post Test) in the form of basic language skills questions. The supporting factors of the bilingual class program include a more enjoyable atmosphere, simple materials, and more innovative learning methods. The inhibiting factors are the lack of learning facilities and limited implementation time.